The Sensitivity of Gel Electrophoresis as a Detector of Genetic Variation - Ramshaw, John A. M. (1979)
Three experiments based on an idea of Youderian have been performed to determine the proportions and kinds of amino acid substitutions that are detected by gel electrophoresis when applied to surveys of protein variation in populations. The experiments involved applying the sequential method of electrophoresis under several conditions of pH and gel concentration to a large sample of human hemoglobins with known amino acid substitutions. In the first experiment, a random sample of 20 different hemoglobin variants was studied, and these were separated into 17 distinct electrophoretic classes by three sequential gel conditions, thus giving a detectability of 85%. A single pass under standard conditions detected eight classes. The second experiment compared groups of substitutions that were chemically identical, but in different positions in the α and β chains, while the third experiment compared pairs of substitutions that were charge equivalent, but chemically different at the same chain position. The sequential method distinguished 90% of all chemically identical substitutions when they were at different chain locations, and four out of five charge equivalent but chemically different substitutions at the same site. Examination of the location of each substitution in the three-dimensional structure of hemoglobins showed that interior substitutions usually are less different from Hb A than are surface substitutions and that local interactions with chain and spatial neighbors are sufficient to distinguish substitutions in very similar positions on the outside of the molecule. The "charge ladder" model of electrophoretic classes is clearly incorrect, and it appears that sequential gel electrophoresis as practiced in our Drosophila surveys has detected a substantial fraction of amino acid substitutions if hemoglobin is regarded as a model. This estimate may be modified as other molecules beside hemoglobin are subjected to similar calibration experiments.